Interaction dispersed, participation compromised - McLuskie, Ed (Javnost (Ljubljana), 2015)
Thirty-five years after its release, UNESCO's Many Voices, One World ("The Report") remains a generation's hope that communication bears a relation to democracy down to the concrete interactions of the people. The hope was and is compromised by a parallel history and prehistory of the field called "communication" and "media studies." Participation-as-audiences morphed but still promote versions of "interaction" linked to the latest technologies-thus accommodating economic and cultural power as media- and info-power. Emancipation by new-tech adoption define "communicative interaction" in terms reminiscent of modernization research exporting the West to the rest, today to all. The idea that communicative interaction could thrive within such frames compromised "The Report," leaving the idea of democratic participation subject to recurring myths about the democratizing power of "the new." Reflecting a legacy of conceits since "development" migrated into the field called "communication," media- and info-centric orientations instrumentalise "interaction" and "participation" in a marketplaced world. There, many voices remain situated in the capitalist promise of potential while still-salient definitions of "communication", "information", and "democracy" frustrate "The Report's" aim of a right to communicate, an aim where political consequence suits interactive and authentic publics defining otherwise mediated times.
Keywords: communicative action; communicative rights; Družbeno komuniciranje; Interaction; Interakcija; Javna sfera; MacBride Report; Participacija; Participation; Public sphere; Social communication